A paper life - O'Neal, Tatum 1963- (Harper Entertainment, 2004)
The Academy Award-winning actress shares candid details about growing up with her late alcoholic mother and overbearing father, her volatile marriage to John McEnroe, her near-fatal battle with drug addiction, and her experiences with fellow celebrities, sports figures, and pop culture stars.
Keywords: O'Neal, Tatum -- 1963-; Motion picture actors and actresses -- United States -- Biography; USA; Autobiografie